Real-Time Three-Dimensional Endoscope Shape Monitoring Using Long and Twist-Suppressed Fiber Bragg Grating Sensors - Jang, Minsu; Jeon, Han Jo; Kim, Byung Kook; Moon, Hyowon; Keum, Bora; Kim, Jinseok (Institute of Electrical and Electronics Engineers, 2025)
Standard flexible colonoscopy is a powerful diagnostic tool for detecting colorectal cancer. However, the procedure entirely depends on the skill and perception of the colonoscopist, leading to unpredictable outcomes such as loop formation, potentially leading to severe complications. Consequently, there is a growing demand for a real-time shape monitoring system for colonoscopes. Despite various research efforts and commercial products that use magnetic sensors, challenges such as signal vulnerability, cost, and limited applicability persist. Optical fiber sensors (OFS), which address these drawbacks, are gaining increasing attention. However, measuring the shape of long colonoscopes accurately remains challenging for OFS due to twist-induced noise. In this study, we developed a twist-suppressed fiber Bragg grating (FBG) sensor to measure long 3-D shapes by enhancing the linearity of the sensor and introducing a node-type structure. We also introduced an insertion length measurement algorithm for stable monitoring with this shape sensor. The twist-suppressed shape sensor exhibited a torsion angle suppression of 92% compared to conventional FBG shape sensors, achieving a torsional angle of 0.48°/cm. We evaluated the performance of the sensor by measuring bending directions and various loop shapes. Clinical tests with FBG sensors demonstrated their potential for real-time monitoring and reducing the time required for loop reduction. A colonoscopic monitoring system capable of precise shape measurements can facilitate safer and quicker procedures.